Photosynthetic and Lipogenic Response Under Elevated CO2 and H2 Conditions—High Carbon Uptake and Fatty Acids Unsaturation - Butti, Sai Kishore; Venkata Mohan, S. (Frontiers in Energy Research, 2018)
Microalgae are most versatile organisms having ability to grow under diverse conditions and utilize both organic and inorganic carbon sources. Microalgal photosynthesis can be employed to transform carbon dioxide (CO2) into essential bioactives and photofuels. In this study, microalgal growth under modified headspace gas compositions which are CO2 + H2 (1:1), CO2, H2 and Air was evaluated to determine the photosynthetic efficiency and bioactives production. A marked enhancement was observed in quantum yield (Fv/Fm: 0.77) and CO2 biosequestration rate (0.39 g.L.-1d−1) under CO2 + H2 headspace gas condition as compared to the other experimental variations. The chemoselective functioning of Rubisco under varying gas concentrations was determined, where elevated CO2 conditions negate the oxygenase activity under a high CO2/O2 ratio which enabled higher CO2 sequestration. The enhanced CO2 sequestration and altered redox conditions through H2 addition under the monophasic operation have also led to a higher average degree of unsaturation (DU) and carbon chain length (CCL) of the fatty acids produced. This study provides an approach to augment photosynthetic efficiency and lipogenesis through non-genetic modifications along with the feasibility to cultivate microalgae in integration with industrial flue gases. Exploiting the true potential of microalgae would provide sustenance from climatic changes and environmental pollution concurrently producing biobased products analogous to the fossil-derived products.